2011
DOI: 10.1159/000320860
|View full text |Cite
|
Sign up to set email alerts
|

Cytological Characteristics of Pulmonary Pleomorphic and Giant Cell Carcinomas

Abstract: Objective: To establish cytological features of pulmonary pleomorphic carcinoma (PC) or giant cell carcinoma (GC), we evaluated the cytological characteristics of these tumors using a multidisciplinary approach. Study Design: Samples from 13 surgically resected and histologically confirmed PC or GC patients were collected from our institutes. Eight cases without prior chemotherapy before surgery were selected, and cytological features were analyzed. Results: The background contained numerous lymphocytes and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…There have been only a few reports of cytological analysis in cases of pulmonary PC 14-16. Most of the previous cytological reports have revealed similar findings.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…There have been only a few reports of cytological analysis in cases of pulmonary PC 14-16. Most of the previous cytological reports have revealed similar findings.…”
Section: Discussionmentioning
confidence: 91%
“…To date, the cytological findings of fine needle aspiration (FNA) of PC have rarely been described with only a few case reports 14-16. The purpose of this study was to investigate the cytomorphological characteristics of PC together with its corresponding histological characteristics, with the aim of improving the preoperative diagnosis of PC.…”
mentioning
confidence: 99%
“…In cytological preparations, giant cells typically appear as single cells or in flat loose clusters, and occasionally in fascicles. 15 Another specific feature known about this malignancy is the presence of a phenomenon called emperipolesis: collections of polymorphonuclear leukocytes within the giant cells, apparently phagocytosing cytoplasmic contents. 6 However, the etiology of emperipolesis in GCCL is unclear.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…Moreover, Fishback et al reported that only 1 of 48 cases of giant cell carcinoma had SCLC component (13). Only a few reports regarding the cytological features of pleomorphic carcinoma have been published (14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%